Knowledge of Tooth Discoloration and Tooth Bleaching amongst Adult Patients Visiting a Dental Hospital in Kathmandu, Nepal - Joshi, Rojin; Gautam, Suman; Joshi, Barsha (Nepal Medical College Journal, 2024)
A beautiful smile increases the self-confidence and well being of an individual. Tooth discoloration is one of the cause for a patient to stop smiling, be less interactive with other people and the person might feel neglected from the society. Many people don’t know about the various causes of tooth discoloration and the treatment options. Bleaching is a very conservative method to whiten the teeth. Until now limited studies have been done to assess the knowledge of tooth discoloration and vital tooth bleaching in context to Nepal. Hence, the objective of this study was to assess the knowledge of tooth discoloration and tooth bleaching amongst adult patients. This cross sectional study was done on 326 patients of 18 years and above. Personal interviews using a structured and validated questionnaire were conducted to collect the following information: demographic data, the participant’s level of satisfaction of their tooth color, the participant’s level of knowledge on tooth discoloration and tooth bleaching. Data were analyzed using Chi square test and descriptive statistics were calculated. It was found that majority of the study participants (63.8%) were satisfied with the color of their teeth and most of them (58.9%) had not heard about tooth bleaching. It was seen that there was no association of different aspects of bleaching as well as etiology of tooth discoloration with gender, age group, level of education and marital status.